Fault classification and location on high voltage lines using the random forest algorithm - الختيار, راما; جورج اسبر; علي السيد (Latakia University Journal -Engineering Sciences Series, 2023)
Accurate identification of fault type and location in electrical power transmission lines contributes to improving the reliability of the electric power system. In this research, the fault type and location in 230 kV high-voltage line were determined using the random forest algorithm, which is characterized by its high accuracy and its high ability to handle a large number of data, by using the amplitudes of the currents and voltages signals measured from one end of the transmission line, where they were used as input features for different faults on the line with different fault parameters (fault distance and resistance). The results showed the ability of the proposed algorithm to classify the type of fault and determine its location in the transmission line with an accuracy of 100% For the process of determining the type of fault, the maximum error in determining the fault location is 0.402 km